Lactation in quarantine: The (in)visibility of human milk feeding during the COVID-19 pandemic in the United States - Mathilde Cohen; Corinne Botz (BMC, 2022)
Abstract Background In response to the COVID-19 pandemic, billions of people were asked by their state and local governments not to go to work and not leave the house unless they had to. The goal of this qualitative study was to collect the lived experiences of a small group of parents and lactation professionals in the United States about what it was like to feed babies human milk under these conditions of quarantine. Methods This project is a social constructionist analysis of lactation narratives of 24 parents feeding their children human milk and 13 lactation professionals. They were interviewed remotely in 2020-21 via videoconferencing about their experiences and perspectives on the pandemic's effect on lactation. Additionally, photographs of 16 of the parents are provided to visualize their practices and how they chose to represent them. Results Four interrelated themes were identified in participants' narratives about how they experienced and made sense of human milk feeding during the pandemic: the loneliness of lactation during the pandemic, the construction of human milk as a resource to cope with the crisis, the (in)visibility of lactation amidst heightened multitasking, and the sense of connection created by human milk feeding at a time of unprecedented solitude. Conclusions While the pandemic may have had both positive and negative effects on lactation, it exposed continuing inequities in infant feeding, generating new forms of (in)visibility for lactating labor. Going forward, one lesson for policy and lawmakers may be that to adequately support lactation, they should take cues from the families who had positive experiences during the crisis. This would call for systemically overhauling of US laws and policies by guaranteeing: universal basic income, paid parental leave for at least six months, paid lactation leaves and breaks, affordable housing, universal health care, subsidized childcare programs, and equal access to high-quality, non-discriminatory, and culturally appropriate medical care-including lactation counseling-, among other initiatives.